685 high digestives hemorrhages studied by fibroscopy - Sojo, Enrique; Estapé, Gonzalo; Pike, Alexander (Cirugía del Uruguay, 1977)
This paper contains the results of diagnosis by fibroscopy in 685 high digestive hemorrhages. Statistical analysis indicates a high incidency of acute lesions ( 51.3 % of intrahemorrhagic studies) which have neither dinical nor radiological expresion. Intrahemorrhagic fibroscopic examination is important _in establishing diagnosis of these brief evolutive lesions. There is no doubt that the multiple causes of stress and the increasing ingestion of medicines which are aggresive to the mucosa, are the explanation of the frequency with which this lesions is found. Other causes of hemorrhage which can only be detected by fibroscopy and which have so far been practícally unknown, are analyzed. (Telangiectasies, ulcer due to suture material, neoplasm of duodenum). Diagnostic effectiveness obtained through fibroscoPY in intrahemorrhagic examinations in current case material was as high as 98 % with respect to topography of lesion and 97 % with respect to capacity of identifying lesiona! type. Different therapeutic methods employed endoscopically for hemostatic purposes are analyzed ( cauterization polipectomy, instillation of local vaso-constrictors).